Hubungan Kualitas Tidur dengan Subjective Well-Being pada Mahasiswa Kedokteran dalam Menghadapi Pembelajaran Tatap Muka di Bandar Lampung - Fauziah, Syifa Alya; Triwahyuni, Tusy; Setiawati, Octa Reni (MAHESA : Malahayati Health Student Journal, 2023)
ABSTRACT Subjective well-being is a person's assessment of the level of quality of life from their point of view or emotional experience. Such as satisfaction, positive affect and low negative affect. In medical faculty students, one of the factors that affect subjective well-being is the quality of sleep is a person's satisfaction with sleep, so that people do not show fatigue or drowsiness. Knowing the relationship between sleep quality and subjective well-being in medical students in facing face-to-face learning in Bandar Lampung. Quantitative research with analytic survey design and cross-sectional design. The research sample amounted to 139 medical students in Bandar Lampung. The measuring instruments used were student demographic data and Positive Affect Negative Affect Schedule (PANAS), Satisfaction With Life Scale (SWLS) and Pittsburgh Sleep Quality Index (PSQI). Most respondents had a moderate level of sleep quality (59.7%%) and subjective well-being (67,6%). The correlation analysis results obtained a p-value of 0.000 and a r-value of 0.404. There is a relationship between sleep quality and Subjective well-being in medical students in facing face-to-face learning in Bandar Lampung. Keywords: Sleep Quality, Subjective Well-Being, Medical Students.  ABSTRAK Subjective well-being merupakan penilaian seseorang terhadap tingkat kualitas hidup dari sudut pandang atau pengalaman emosionalnya. Seperti kepuasan, afek positif dan rendahnya afek negatif. Pada mahasiswa fakultas kedokteran salah satu faktor yang mempengaruhi subjective well-being adalah kualitas tidur merupakan kepuasan seseorang terhadap tidurnya, sehingga orang tidak menunjukan kelelahan atau mengantuk. Mengetahui hubungan kualitas tidur dengan subjective well-being pada mahasiswa kedokteran dalam menghadapi pembelajaran tatap muka di Bandar Lampung. jenis penelitian kuantitatif dengan desain survei analitik dan rancangan cross-sectional. Sampel penelitian berjumlah 139 mahasiswa kedokteran di Bandar Lampung. Alat ukur yang digunakan adalah data demografi mahasiswa dan Positive Affect Negative Affect Schedule (PANAS), Satisfaction With Life Scale (SWLS) dan Pittsburgh Sleep Quality Index (PSQI). sebagian besar responden memiliki tingkat kualitas tidur sedang (59,7%%) dan subjective well-being (67,6%). Hasil analisis korelasi didapatkan p-value 0,000 dan nilai r 0,404. Terdapat hubungan kualitas tidur dengan subjective well-being pada mahasiswa kedokteran dalam menghadapi pembelajaran tatap muka di Bandar Lampung. Kata Kunci: Kualitas Tidur, Subjective Well-Being, Mahasiswa Kedokteran.